Peran Kepemimpinan Kepala Sekolah, Pengambilan Keputusan, Dan Budaya Organisasi Terhadap Disiplin Kerja - Ahmad Khosyi'in (Chalim Journal of Teaching and Learning (CJoTL), 2021)
This study aims to determine the influence of principal leadership, decision-making, and organizational culture to the working discipline of Muhammadiyya High School 5 Todanan Blora. This research is the quantitatively research. The population of research is all educators and education personnel of Muhammadiyyah High School 5 Todanan Blora. A research sample size of 28 educators and educational personnel, selected based on purposive sampling techniques. Instrument preparation is made in the form of a questionnaire, with an answer of 1-5 scale, consisting of 20 grains. The instruments used to collect data are those that qualify for the construction analysis and valid status. Its reliability is calculated by the Cronbach Alpha technique. Data analysis uses multiple linear regression techniques to test the research hypothesis. The results of the study proved: (1) There is no influence between the principal leadership of the work discipline; (2) There is no influence between the decision making of the work discipline; (3) There is no influence between the organizational culture of the work discipline; (4) There is no influence between the leadership of the principal, decision-making, and organizational culture together with the work discipline.